HSP90 is a target protein for ubiquitination in Giardia intestinalis - Chaparro Gutiérrez, Jenny Jovana; Wasserman, Moisés (Revista Colombiana de Ciencias Pecuarias, 2011)
Previous studies have demonstrated the existence and expression of genes essential to the process of protein ubiquitination in Giardia intestinalis, indicating that the ubiquitin-proteasome system may be involved in the degradation of proteins during its life cycle of the parasite. In this study, purification of ubiquitin was conducted from protein extracts of G. intestinalis trophozoites. Then, an anti-ubiquitin specific antibody was obtained to standardize an assay for the detection and evaluation of ubiquitination patterns. Finally, HSP90 was identified as an ubiquitinated protein in this protozoan. This post-translational modification could have regulatory effects associated with the functionality of the protein or its turnover to regulate key molecular events during the parasite’s life cycle. Key Words: protozoan, thermic shock protein, ubiquitin. Resumen Estudios previos han demostrado la existencia y expresión de genes esenciales para el proceso de ubiquitinación de proteínas en Giardia intestinalis, indicando que el sistema ubiquitina-proteosoma puede estar involucrado en el proceso de degradación de proteínas de este parásito durante su ciclo de vida. En el presente trabajo se realizó la purificación de ubiquitina a partir de extractos proteicos de trofozoítos de G. intestinalis, se produjo un anticuerpo anti-ubiquitina específico que permitió la estandarización de un ensayo para la detección y evaluación de los patrones de ubiquitinación, y se identificó la HSP90 como una proteína ubiquitinada en este protozoario. Esta modificación post-transduccional puede tener efectos regulatorios asociados con la funcionalidad de la proteína o con el recambio para regular eventos moleculares claves durante el ciclo de vida del parásito. Palabras clave: protozoario, proteína de choque térmico, ubiquitina. Resumo Estudos anteriores demonstraram a existência e expressão de genes essenciais para o processo de ubiquitinação de proteínas em Giardia intestinalis, indicando que o sistema ubiquitina-proteassoma podem estar envolvidos na degradação de proteínas do parasita durante seu ciclo de vida. Neste trabalho, foi realizada a purificação da proteína ubiquitina de extratos de trofozoítos de G. intestinalis, foi produzido um antiicorpo anti-ubiquitina específico que permitiu a padronização de um ensaio para a detecção e avaliação de padrões de ubiquitinação e foi identificado a HSP90 como uma proteína ubiquitinada no protozoário. Esta modificação pós-transducional pode ter efeitos regulamentares associados com a funcionalidade das proteínas ou com o a substituição para regular eventos moleculares importantes durante o ciclo de vida do parasita. Palavras-chave: protozoários, proteínas de choque térmico, ubiquitina.